Effects of deficit irrigation on some yield characteristics of sweet corn (Bangladesh Journal of Botany, 2008)
This study was made to determine the influence of deficit irrigation on drip irrigated sweet corn in 1998 and 1999 in Sanliurfa, Turkey. Water was applied to sweet corn as 100, 90, 80 and 70% of evaporation from a Class A Pan (Epan). Applied irrigation water was 610-876 mm and 612-889 mm in 1998 and 1999, respectively. Plant height, ear length, number of kernels per ear and single fresh ear weight values were the highest at 100% Epan whereas the lowest values were found at 70% Epan in both the years. Water savings were 11.30, 20.89 and 30.36% in 1998 and 10.91, 21.14, 31.15% in 1999 for 90, 80 and 70% of Epan, respectively. The highest fresh ear yields (14.76 and 14.17 t ha-1) were obtained at 100% Epan, whereas minimum fresh ear yields (9.15 and 8.84 t ha-1) were found at 70% of Epan in 1998 and 1999, respectively. Despite the reduction of fresh ear yield, the number of marketable ears at 10% water deficiency (90% Epan) was still high and acceptable for sweet corn production in the Harran Plain of Turkey. Key words: Deficit irrigation, Water saving, Sweet corn, Yield characteristics doi:10.3329/bjb.v37i2.1718 Bangladesh J. Bot. 37(2): 127-131, 2008 (December)